(untitled) (The Research of Medical Science Review, 2025)
Background: Oral Cancer affects patients as well as their family members and it is a serious, life-threatening disease. Additionally, caregivers are crucial to the treatment of oral cancer patients. Primary caregivers are severely burdened by the side effects and consequences of oral cancer treatment. Oral cancer patients often require extensive wound care, which places a significant burden on primary caregivers. Objective: To evaluate the impact of a wound dressing intervention on the care burden faced by the main caregiver of patients with oral cancer Methods and Material: Several electronic databases were used in the literature review, including Google Scholar, Academia, Science Direct, Cumulative Index to Nursing and Allied Health Literature, and PubMed. The literature review procedure was recorded using the PRISMA flowchart approach. In the final review, which covered the last five years, we included 09 out of 235 papers that met the inclusion criteria and examined how wound dressing intervention effects on caregiver burden or primary caregiver of oral cancer patients. To detect common results across trials, data were combined using quantitative approaches. Result: The research indicates that the wound dressing intervention significantly reduced the burden of care among caregivers of oral cancer patients. Conclusion: The study's findings demonstrate that the wound dressing intervention effectively reduced the burden on patients with oral cancer who had primary caregivers. The significant reduction in post-intervention burden makes it abundantly evident that systematic wound care management is crucial to lowering carer stress and improving their general health.